2021
DOI: 10.31940/jbk.v17i1.2320
|View full text |Cite
|
Sign up to set email alerts
|

Good Corporate Governance: Does The Timeliness of Financial Reporting Has an Effect to The Investors’ Reaction?

Abstract: This research aims to find out the influence of independent committee boards, audit committee repats, foreign ownership, and audit quality on the timeliness of financial reporting and their impact on investors' reactions both directly and indirectly. This research uses a quantitative method with population and sample of companies registered in Jakarta Islamic Index (JII). Data will be processed using path analysis using IMB SPSS Statistic 22 software. Based on the results of this research, it is known that dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…So it can be concluded that the audit quality variable has a significant positive effect on the quality of the company's financial reporting. The results of this study are in line with research conducted by Irwandi (2020), Furwanti et al (2021), and Kartika and Pramuka (2019) which states that the audit quality variable has a significant positive effect on the quality of the company's financial reporting.…”
Section: Audit Quality On Financial Report Qualitysupporting
confidence: 89%
“…So it can be concluded that the audit quality variable has a significant positive effect on the quality of the company's financial reporting. The results of this study are in line with research conducted by Irwandi (2020), Furwanti et al (2021), and Kartika and Pramuka (2019) which states that the audit quality variable has a significant positive effect on the quality of the company's financial reporting.…”
Section: Audit Quality On Financial Report Qualitysupporting
confidence: 89%